Identification of Skills among BIM Coordinators in the Malaysian Construction Industry - Ng Hua Tai; Aryani Ahmad Latiffi (Journal of Technology Management and Business, 2022)
Building Information Modelling (BIM) is the current trend in the Malaysian construction industry. It has evolved from ‘What is BIM?’ to ‘How to use BIM?’ In the current market, numerous positions have been created for organisations to implement BIM. In Malaysia, the most common BIM position is the BIM Coordinator. However, there is a lack of information when it comes to the necessary BIM skill sets. Many positions are created for the sake of fulfilling contract purposes since the BIM implementation is mandated by the local government. Hence, this paper aimed to identify the skills required for BIM coordinators by reviewing papers by researchers throughout the decade. The identified BIM skills can give a brief concept of the necessary requirement to become a BIM coordinator. Also, the prospective BIM coordinators can use the identified BIM skills in this paper as a guide. This paper has identified four main skills that can be categorised as both BIM technical and non-technical skills namely BIM tool skills, multi-trade coordination, communication as well as collaboration.